Evaluating impact damage to fabric-based personal armor by infrared NDT - Budadin O. N. Oleg Nikolaevich; Kozelskaya S. O.; Kaledin V. O. Vladimir Olegovich; Vavilov V. P. Vladimir Platonovich; Kuimova M. V. Marina Valerievna (2019, 2019)
Title screen